Plastic: A Boon but Also a Curse to the Environment - Panthi, B.; Koirala, I.; Panthi, N. (Journal of Nepal Physical Society, 2023)
Besides being a significant part of our daily lives, plastic has a detrimental negative environmental impact thanks to its non-degradable nature. The dependency and impacts of plastics have been carefully analyzed in order to investigate their effects on the environment. The paper studies large scale production, use and the impacts of plastics on the environment. Investigation on the ways plastics affect soil, atmosphere, water and health of living being have been done. Similarly, the statistical data about their use and effects have been presented and future projections have been made.